2017
DOI: 10.1007/s10461-017-1683-z
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter European Prevalence Study of Neurocognitive Impairment and Associated Factors in HIV Positive Patients

Abstract: We conducted a cross-sectional study in 448 HIV positive patients attending five European outpatient clinics to determine prevalence of and factors associated with neurocognitive impairment (NCI) using computerized and pen-and-paper neuropsychological tests. NCI was defined as a normalized Z score ≤−1 in at least 2 out of 5 cognitive domains. Participants’ mean age was 45.8 years; 84% male; 87% white; 56% university educated; median CD4 count 550 cells/mm3; 89% on antiretroviral therapy. 156 (35%) participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
3
28
1
4
Order By: Relevance
“…Limitations to CIPHER study methodology and Cogstate in general have been discussed in earlier reports, 11,25 but some deserve further mention here. Notably, selection biases may have arisen as a result of our opportunistic sampling strategy, with patients choosing to participate in the study on the basis of their own concerns and self-perceived cognitive symptoms.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Limitations to CIPHER study methodology and Cogstate in general have been discussed in earlier reports, 11,25 but some deserve further mention here. Notably, selection biases may have arisen as a result of our opportunistic sampling strategy, with patients choosing to participate in the study on the basis of their own concerns and self-perceived cognitive symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…In our recently published report of the same study population, we showed that severe depressive symptoms were associated with cognitive impairment, particularly on timed tests. 11 A controlled intervention to improve patients' depression or anxiety symptoms might tease out the effect of low of mood on subjective and objective cognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations